Research and Development of youth networks for crime and victimization prevention through social media processes: การวิจัยและพัฒนาเครือข่ายเยาวชนเพื่อป้องกันการกระทำผิดและตกเป็นเหยื่ออาชญากรรมด้วยกระบวนการสื่อสังคมออนไลน์ - Pothisuwan, Sanchai (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2020)
This study - the Research and development of youth networks for crime and victimization prevention through social media processes – aimed to study patterns of participation in activities or social interaction of children and youth. According to the concept of social bonding theory by using social media as a mean to communicate positive energy in the form of social psychology to protect oneself from committing an offense or becoming a victim of a crime. Public relations and giving incentives via social media have been executed by forming a network to create engagement through social media. Therefore, it is able to protect and prevent juvenile delinquency which related to social situations in this digital age. The results of the study revealed that there was a network sustainability establishment, which initially started by creating activities or disseminating knowledge that promoted continuous interaction between networks on social media in order to create awareness and trends in the online society. In the workshop, the activity was proactively organized in the form of Road Show activities which provided activities in various school and also organized activities in forms of positive energy youth festival to provide knowledge and skills in protecting oneself from committing crimes and becoming a victim of crime, including collecting network registers from participants to build up and further expand the operating results. The quantitative study found that the sample group agreed that the text, images, videos and other medias which relating to the information on protecting oneself from committing an offense or becoming a crime victim published via social media were significantly useful at a high level The video media was produced as a symbol of inspirational positive communication to the network.